Effects of environmental conditions, human activity, reproduction, antler cycle and grouping on fecal glucocorticoids of free-ranging Pampas deer stags (Ozotoceros bezoarticus bezoarticus) - Pereira, RJG; Duarte, JMB; Negrao, J. A. (Elsevier B.V., 2006)
In this study, a commercial enzyme immunoassay (EIA) was validated in detecting glucocorticoids in Pampas deer feces, in order to investigate the influence of several factors on the adrenocortical function. Fecal samples, behavioral data and information concerning male grouping and antlers status were collected at a monthly basis during a 1 year period from free-ranging stags living at Emas National Park, Brazil (18 degrees S/52 degrees W). The results revealed that concentrations of fecal glucocorticoids in winter were significantly higher than those corresponding to spring and summer. In addition, dry season data presented higher levels than during the wet season. Significant difference was found between fecal levels of breeding stags in summer and nonbreeding stags, whereas no difference was observed between breeding stags in winter and nonbreeding stags. on the other hand, males from areas with frequent human disturbance exhibited higher glucocorticoid concentrations and flight distances than individuals from areas of lower human activity. Males with antlers in velvet had elevated levels compared with animals in hard antler or antler casting. Also, we found that glucocorticoid levels were higher in groups with three or more males than in groups with only one male. The flight distances showed positive correlation with fecal glucocorticoid. These data indicate that fecal glucocorticoid provides a useful approach in the evaluation of physiological effects of environment, inter-individuals relationship and human-induced stressors on free-ranging Pampas deer stags. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Pampas deer; Ozotoceros bezoarticus; stress; glucocorticoids; feces; enzyme immunoassay; environmental conditions; human activity; reproduction; antler cycle; male grouping